Hidden and visible realms : early medieval Chinese tales of the supernatural and the fantastic - Liu, Yiqing, 403-444 (Translations from the Asian classics., 2018)
"The Hidden and Visible Realms (Youming lu) is one of the most significant collections of Chinese zhiguai "Records of the Strange" literature. It is distinguished by its varied contents, elegant style of writing, and fascinating stories. This is the first complete English translation of the original, and Zhang has done significant editorial work on the collection, collecting every item that has been attributed to the volume, but placing those of suspect provenance in the appendix. The work is also significant for its early inclusion of Buddhist themes, making it of great interest to scholars of religion of the early medieval period"--